Perhitungan Kapasitas dan Waktu Penggunaan Baterai Lithium-Ion pada Sepeda Listrik dengan Motor BLDC 350 W - Denny Haryanto Sinaga; Muhammad Aulia Rahman Sembiring; Rudi Salman; Olnes Yosefa Hutajulu; Arwadi Sinuraya (Fidelity : Jurnal Teknik Elektro, 2023)
Batteries are one of the most important components in electric vehicles. Batteries are used as an energy source for the entire electrical system and as a place to store electrical energy during charging process. The battery functions to supply electric current in order to operate the electric machine. The lithium-ion battery is a type of secondary battery (rechargeable battery) that can be recharged and is an environmentally friendly battery. This battery has excellent energy storage stability and higher energy density compared to other types of secondary batteries, making this type of battery increasingly attractive for use in electric vehicles. This study aims to design the size of an electric bicycle battery according to its specifications. In addition, an analysis of the calculation of the capacity of the battery to be used and the time for the recharging process is also carried out.